2012
DOI: 10.1007/s10911-012-9261-5
|View full text |Cite
|
Sign up to set email alerts
|

Lactation and Neonatal Nutrition: Defining and Refining the Critical Questions

Abstract: This paper resulted from a conference entitled “Lactation and Milk: Defining and refining the critical questions” held at the University of Colorado School of Medicine from January 18–20, 2012. The mission of the conference was to identify unresolved questions and set future goals for research into human milk composition, mammary development and lactation. We first outline the unanswered questions regarding the composition of human milk (Section I) and the mechanisms by which milk components affect neonatal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
103
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 163 publications
(186 reference statements)
1
103
0
11
Order By: Relevance
“…In beef cattle that are reared by their dam, sons are born bigger and have better post-natal growth than do daughters, but only one out of three studies has shown any evidence of male-biased milk synthesis [44][45][46]. In the absence of post-natal behavioral modifications of prenatal mammary gland programming, the presence and concentration of other milk bioactives such as immunofactors and hormones that influence offspring development [35] may differ in milk produced for sons and daughters. Notably, investigations of sexually dimorphic developmental trajectories, however, overwhelmingly essentialize the role of the mother and sex-biased allocation of maternal resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In beef cattle that are reared by their dam, sons are born bigger and have better post-natal growth than do daughters, but only one out of three studies has shown any evidence of male-biased milk synthesis [44][45][46]. In the absence of post-natal behavioral modifications of prenatal mammary gland programming, the presence and concentration of other milk bioactives such as immunofactors and hormones that influence offspring development [35] may differ in milk produced for sons and daughters. Notably, investigations of sexually dimorphic developmental trajectories, however, overwhelmingly essentialize the role of the mother and sex-biased allocation of maternal resources.…”
Section: Discussionmentioning
confidence: 99%
“…Milk synthesis is unlikely to be at the maternal optimum because of parent-offspring conflict [32][33]. Rather milk reflects a complex physiological and behavioral negotiation between the mother and offspring [34][35]. Functional development of the mammary gland initially occurs during pregnancy and is orchestrated by maternal and placental hormones, particularly placental lactogen, estrogen, and progesterone [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…While having the known major nutrients (proteins, lipids, carbohydrates, vitamins, and minerals) required for "normal" infant growth, formulas lack specific factors that promote human development to the same level as breast milk (1). The importance of breast milk for brain development is particularly highlighted in studies of children born preterm, where significant advantages in neurodevelopment are gained in those fed breast milk during infancy as compared to formula (2,3).…”
mentioning
confidence: 99%
“…One aspect of brain structure where diet-related differences might be expected would be in the integrity of white matter. White matter contains large bundles of myelinated axons and is responsible for transmission of signals between different brain regions, and breast milk and formulas differ in factors that contribute to myelination (1). The structural connectivity provided by white matter tracts is essential for normal brain function, and abnormalities or deficits in white matter have been observed in a wide variety of neurodevelopmental disorders in children (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Recently, a publication in this journal reported on a conference that considered defining and refining critical questions of lactation and milk. One priority established that a focus should be centered on the training of future lactation biologists [4]. We concur with this recommendation.…”
mentioning
confidence: 52%